Yemen through the lens of Hayat Al-Sharif (PlaySpace, 2023)
When I started my photography journey, I travelled through seven governorates to document Yemeni heritage, handcraft and art. I initialized my work with aid from an artisans organization based in Washington DC. After the war started, I have been working with humanitarian projects to illustrate stories of the suffering of Yemeni women and children.